A Critical Study of Saddharmapundarika Sutra : A Message of Peace and Harmonious Coexistence - Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This Research has the three purposes, namely : - 1) to study the history, the contents, the persons and the events in Saddharmapundarika Sutra, 2) to study the significant concepts and Doctrinces in Saddharmapundarika Sutra and 3) to apply the significant concepts and Doctrines in Saddharmapundarika Sutra for to make Peace and Harmonious Coexistence. It is documentary research. From the study, it is found that Saddharmapundarika Sutra was written first in India with Sanskrit Language. It is composed of the prose and the prosody. The significant concept is the Buddha’s one vehicle. The Saddharmapundarika Sutra is spread extensively in many countries such as India, China, Japan and Thailand. Saddharmapundarika Sutra consists of twenty-seven chapters. The substance, the persons and the events are concerning with the great meeting of the Buddha’ s companies, the forecasting etc. Saddharmapundarika Sutra consists of the concepts about the Buddhas, the Bodhisatvas, the good trick and the Dharani (chanting). The significant doctrines in Saddharmapundarika Sutra consist of the Four Noble Truths, the Dependent Origination, the Master’s Ninefold Teaching to be the means for the Buddha’s one vehicle and the Buddhists’ confidences to study and practicse this Saddharmapundarika Sutra and listening of Dharma. The significant concepts in Saddharmapundarika Sutra that can be applied in the society are living for others, helping each other, loving and compassion other, to take mutual benefit, living in society without encroach other, to devote the Religion. The significant doctrines in Saddharmapundarika Sutra that can be applied in the society are the four Noble Truths, Independent origination, communication, believe in other and listening to Dharma.